Profit analysis of pig farming in rural comunities in Minahasa Regency of North Sulawesi - Santa, N. M.; Wantasen, E. (Journal of the Indonesian Tropical Animal Agriculture, 2018)
The objective of this study was to analyze the factors influencing the profit of pig farms in rural communities in Minahasa Regency, North Sulawesi based on output sales orientation for breeding stock and combination of breeding-fattening models. The research was conducted from July to December 2016, using survey method with multistage random sampling technique. The selected locations were three Districts of Sonder, Tombulu and Kakas based on the largest population of pigs involving randomly one hundred respondents. The variables were included profit, prices of corn, concentrate, bran, medicine, vitamin, animal housing depreciation, the number of piglets, farm experience and output sales orientation. Data were analyzed on the basis of unit output price Cobb-Douglas Profit Function using multiple linear regressions. Research showed that input prices of production factor and number of piglets were influenced profit (P<0.01). Partially, the input prices of corn, concentrate, bran, medicine, vitamins, output sales orientation, and the number of piglets influenced profit(P<0.01). Average profits of farm were IDR 942,823.70/month for breeding models and IDR 3,679,833.85/month for combination of breeding-fattening models, with average numbers of sows were 2.25 heads